Body Composition of Elite Soccer Players from Montenegro and Kosovo - Jovan Gardasevic; Dusko Bjelica; Ivan Vasiljevic; Fitim Arifi; Sami Sermaxhaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
This research aimed to determine the differences among the top soccer players of a club in Montenegro, FC Buducnost, and the top soccer players of a club in Kosovo, FC Trepca '89, the champions in their countries, in the anthropometric characteristics and body composition. A sample of 45 subjects was divided into two sub-samples. The first sub-sample of the subjects consisted of 30 soccer players of FC Buducnost of the average age 22.73±4.33, the winners of the Montenegro Championship in the 2016/17 season, while the other sub-sample consisted of 15 soccer players of FC Trepca '89 of the average age 21.80±3.57, the winners of the Kosovo Championship in the 2016/17 season. Soccer players were tested immediately after the end of the 2016/17 competition season. Anthropometric characteristics were evaluated using a battery of seven variables: body height, body weight, waist circumference, triceps skinfold, biceps skinfold, skinfold of the back, abdominal skinfold. The body composition was evaluated using a battery of three variables: body mass index, fat percentage and muscle mass. The standard central and dispersion parameters of all variables were calculated. The significance of the differences between the players of the top two soccer clubs in the anthropometric characteristics and variables for assessing body composition was determined using a t-test for independent samples. It was found that the soccer players of the two mentioned clubs do not have statistically significant differences according to the variables.